The genus Microptila Ris (Trichoptera, Hydroptilidae) in Japan - Ito, Tomiko (Zootaxa, 2017)
The taxonomy of the genus Microptila Ris in Japan is revised. Microptila orienthula Kjærandsen and Ito, 2009, the only East Palearctic species in the genus, is redescribed with new records and two new species, M. genka sp. nov. and M. nakama sp. nov., are described for adults from Ryukyu Islands, far southern Japan, in the Oriental region.